The alarming rise of lifestyle diseases and their impact on public health: A comprehensive overview and strategies for overcoming the epidemic - Ram Kumar Garg (Journal of Research in Medical Sciences)
The rising prevalence of lifestyle diseases, including cardiovascular conditions, diabetes, obesity, and mental health disorders, poses a significant threat to global health. The aim of the study is to highlight the impact of sedentary lifestyles, poor diets, and chronic stress on individuals and communities. It advocates for comprehensive strategies involving public health policies, education, and community engagement. Overcoming challenges through lifestyle modifications and policy interventions is crucial. The study also discusses successful global interventions and their application in low-resource settings to combat lifestyle diseases and improve public health. Lifestyle diseases pose a serious global health threat. Urgent action is needed to address sedentary lifestyles, poor diets, and chronic stress. Coordinated efforts through policy, education, and community engagement are crucial. Promoting healthy habits and leveraging global interventions can lead to significant progress. Collaboration among stakeholders is essential for improving global well-being.